Fractional laser-assisted percutaneous drug delivery via temperature-responsive liposomes. Issue 7 (3rd May 2017) - Fujimoto, Takahiro; Ito, Masayuki; Ito, Shinobu; Kanazawa, Hideko
Abstract: Liposomes are used for transdermal delivery of drugs and vaccines. Our objective was to develop temperature-responsive (TR) liposomes to achieve temperature-dependent, controlled release of an encapsulated drug, and use fractional laser irradiation to enhance transdermal permeability of these liposomes. TR-liposomes prepared using a thermosensitive polymer derived from poly-N-isopropylacrylamide, N, N-dimethylacrylamide, egg phosphatidylcholine, and dioleoylphosphatidylethanolamine, delivered fluorescein isothiocyanate-conjugated ovalbumin (OVA-FITC) as a model drug. Effect of temperature on liposome size and drug release rate was estimated at two temperatures. Transdermal permeation through hairless mouse skin, with and without CO2 fractional laser irradiation, and penetration into Yucatan micro-pig skin were investigated using Franz cell and fluorescence microscopy. Dynamic light scattering showed that mean liposome diameter nearly doubled from 190 to 325 nm between 37 and 50 °C. The rate and amount of OVA-FITC released from TR-liposomes were higher at 45 °C that those at 37 °C. Transdermal permeation of OVA-FITC across non-irradiated skin from both TR- and unmodified liposomes was minimal at 37 °C, but increased at 45 °C. Laser irradiation significantly increased transdermal permeation of both liposome groups at both temperatures. Fluorescence microscopy of frozen biopsy specimens showed deeper penetration of FITC from unmodified liposomes compared to that from polymer-modified liposomes. Rhodamine accumulation was not observed with polymer-modified liposomes at either temperature. Temperature-dependent controlled release of an encapsulated drug was achieved using the TR-liposomes. However, TR-liposomes showed lower skin permeability despite higher hydrophobicity. Fractional laser irradiation significantly increased the transdermal permeation. Additional studies are required to control liposome size and optimize transdermal permeation properties.